Analysis of ESG Disclosure and its Impact on Firm Value in Southeast Asia - Mela Nofaliska Panjaitan; Dian Purnama Sari (JENOVA : Journal of Economics, Finance, Accounting, and Organizational Advancement, 2025)
This study examines the effect of Environmental, Social, and Governance (ESG) disclosure on firm value in Southeast Asia by considering corporate governance quality and firm size as control variables. Using a quantitative approach, this study analyzes panel data from 30 publicly listed companies across six ASEAN countries during the 2021–2023 period, resulting in 90 firm-year observations. ESG disclosure is measured using ESG scores obtained from Refinitiv/MSCI, while firm value is proxied by market capitalization. Corporate governance is measured using the ASEAN Corporate Governance Scorecard, and firm size is proxied by the logarithm of market capitalization. The data were analyzed using multiple linear regression. The results show that the regression model is statistically significant, with an R² value of 0.892 and an F-statistic of 236.6 (p < 0.001). Partially, ESG disclosure has a positive but statistically insignificant effect on firm value (β = 0.046; p = 0.358). The ASEAN CG Score has a significant negative effect (β = -0.169; p = 0.015), while firm size has the strongest positive and significant effect (β = 13.93; p < 0.001). These findings indicate that Southeast Asian capital markets have not fully internalized ESG disclosure as a determinant of firm value. Instead, investors appear to place greater emphasis on firm size as an indicator of stability and growth potential. This study contributes to ESG literature by highlighting the need for stronger standardization and substantive disclosure quality in Southeast Asian sustainability reporting.